Upaya Meningkatkan Kemampuan Berhitung melalui Permainan Kotak Pintar pada Anak Usia Dini - Yaie, Feggi Ica Jantrie Yaie; Taty Fauzi; Dessi Andriani (Universitas Lancang Kuning, 2022)
In improving children's cognitive, a game is needed so that it stimulates the ability to count. Based on this, the problem to be investigated in this study is how children's numeracy skills can be increased. The purpose of this study is to prove that children's numeracy skills can be improved through smart box games. The approach used in this research is quantitative with the type of classroom action esearch. Data collection methods used in this study were observation, interviews and documentation. The results of this study are: increasing the numeracy ability of children in group B in TK Kartika II 38 applying the smart box game obtained from the analysis of children's numeracy skills in cycle I obtained an average level of developmental achievement score 14 in the category of starting to develop, then seen in cycle I the average level of achievement in the development of numeracy was 34.33 and in the pre-cycle the score was 20.33, this showed an increase while in cycle II the overall numeracy ability of children was 42.17 in the very well developed category so that in the second cycle there was an increase of 7, It was concluded that at the end of the second cycle the research was said to be successful because the criteria for success had been reached according to the agreement between the researchers and the collaboration.